096 Inclusion body myositis: a diagnostic challenge. Issue 3 (9th February 2012) - Brady, S; Squier, W; Hilton-Jones, D; Sewry, C; Holton, J L
Abstract : Background: The currently accepted diagnostic criteria for inclusion body myositis (IBM) comprise pathological and clinical elements. However, the pathological features are not specific to IBM and in many clinically typical cases may be absent. A variety of proteins more commonly associated with neurodegenerative diseases have been found to accumulate in muscle fibres in IBM. The benefit of staining for these proteins in the diagnosis of IBM is unknown. We propose that these protein accumulations may assist in the diagnosis of IBM and help in differentiating it from other myopathies. Aims: To identify the most sensitive histochemical technique available to UK diagnostic pathology laboratories for detecting such protein inclusions and to determine their sensitivity and specificity for the diagnosis of IBM. Methods: We identified six cases of pathologically definite IBM according to the current criteria and six normal control cases. All cases had been assessed clinically and had undergone a biopsy at the National Hospital for Neurology and Neurosurgery. A number of neurodegenerative proteins and inflammatory markers were identified that may be of diagnostic significance. Antibodies to these proteins were optimised using control tissue known to contain the protein of interest. Initial results: Protein inclusions found in IBM were labelled with an antibody to p62, an adaptor protein which binds ubiquitin and regulates signalling cascades through ubiquitination. These inclusions were not found in the normal controls. Further work to quantify the abnormalities in IBM and disease controls will be undertaken before any of these markers can be recommended for diagnostic use.